Dog Tethering in Slovakia: Legal, Ethical and Behavioral Aspects and Dog Welfare Implications - Daniela Takáčová; Lenka Skurková; Lýdia Mesarčová; Lenka Lešková; Lucia Kottferová; Anna Packová; Dávid Vajányi; Jana Kottferová (Animals, 2021)
Long-term tethering of dogs, or their keeping under unsuitable conditions can result in issues related to changes in their behavior as they may not satisfy their basic needs of life. These needs are discussed in this paper, along with cases when dogs unnecessarily have to endure cruelty and pain. The unavoidable tethering of a dog must not cause trauma and must be arranged in a way that it guarantees physical comfort. Failure to meet the basic needs of an animal may result in manifestation of fear and subsequent aggressiveness. Owners of animals are responsible for their life and health, and their obligations include eliminating the possibility of them hurting themselves or other beings. The relevant adopted legislative provisions should provide protection to animals and be enforceable, which currently appears rather difficult. Controlling and observation of the legislative provisions related to the tethering of dogs raises some difficulties for animal protection inspectors. It is necessary to focus on the specificities of keeping conditions of various dog breeds and on their individual features. Based on research and the relevant Slovak legislative provisions, this paper discusses various views on the practice of tethering dogs from the point of view of public safety and the ethical consequences of permanent dog tethering. Data on dog tethering in Slovakia were evaluated based on a survey and Slovak legal rules governing this issue were analyzed along with various views of public safety and the ethical consequences of permanent dog tethering.